From victims to actors: The role of children and young people in flood recovery and resilience. (May 2018) - Mort, Maggie; Walker, Marion; Williams, Alison Lloyd; Bingley, Amanda
Following a series of recent devastating storms across England with large numbers of homes and businesses evacuated, and despite widespread consensus that further severe flooding is expected, a large section of the population continues to be excluded from developments in flood risk management. We argue that the absence of children and young people from assessments of both the effects of flooding and ways in which it can be mitigated, undermines the effectiveness and legitimacy of policy making. Drawing on in-depth participative research with two groups of flood-affected children and young people we show the range of ways in which they are affected by flooding, some ways they can be better supported, and then how their valuable experience can help shape positive change in policy and practice before, during and after floods. Children developed Flood Manifestos for Change in a direct challenge to their omission from flood governance. The Manifestos and the steps children took to advocate for them can be seen as acts of citizenship, highlighting the capacities of children and young people as flood actors, rather than flood victims.